Acquiring sepsis competencies through simulation-based learning bundle during intermediate care unit internship. Issue 5 (5th February 2021) - Fernández-Ros, Nerea; Alegre, Félix; Huerta, Ana; Gil-Alzugaray, Belén; Landecho, Manuel F.; García, Nicolás; Quiroga, Jorge; Lucena, Juan Felipe
Abstract : Abstract: Intermediate care units (ImCUs) have been shown as appropriate units for the management of selected septic patients. Developing specific protocols for residents in training may be useful for their medical performance. The objective of this study was to analyze whether a simulation-based learning bundle is useful for residents while acquiring competencies in the management of sepsis during their internship in an ImCU. A prospective study, set in a tertiary-care academic medical center was performed enrolling residents who performed their internship in an ImCU from 2014 to 2017. The pillars of the simulation-based learning bundle were sepsis scenario in the simulation center, instructional material, and sepsis lecture, and management of septic patients admitted in the ImCU. Each resident was evaluated in the beginning and at the end of their internship displaying a sepsis-case scenario in the simulation center. The authors developed a sepsis-checklist that residents must fulfill during their performance which included 5 areas: hemodynamics (0–10), oxygenation (0–5), antibiotic therapy (0–9), organic injury (0–5), and miscellaneous (0–4). Thirty-four residents from different years of residency and specialties were evaluated. The total median score (interquartile range) increased significantly after training: 12 (25) vs 23 (16), P = .001. First-year residents scored significantly lower than older residents at baseline: 10 (14) vs 14.5 (19), P = .024. However, the performance at the end of the training period was similar in both groups: 21.5 (11) vs 23 (16), P = 1.000. Internal Medicine residents scored significantly higher than residents from other specialties: 18 (17) vs 10.5 (21), P = .007. Nonetheless, the performance at the end of the training period was similar in both groups: 24.5 (9) vs 22 (13), P = 1.000. Combining medical simulation with didactic lectures and a rotation in an ImCU staffed by hospitalists seems to be useful in acquiring competencies to manage critically ill patients with sepsis. We designed a checklist to assure an objective evaluation of the performance of the residents and to identify those aspects that could be potentially improved. Abstract : Supplemental Digital Content is available in the text